AN EMPIRICAL STUDY OF CONFIRMATORY FACTOR ANALYSIS SUCCESSFUL ADOPTION OF HUMAN RESOURCE ANALYTICS IN INDIAN ORGANIZATIONS - SAAEMAAKHTAR; KUMAR SHASTRI, DR. RAJESH (The journal of contemporary issues in business and government, 2022)
The Main purpose of this research is to assess the extent of awareness of Human Resource Analytics among HR Managers at various levels in various firms in India. Design/methodology/approach:-To collect data a combination of quantitative and qualitative research methodologies is used. Data is gathered specifically from various levels of management in selected organizations. Descriptive data analysis is presented in relation to the level of awareness, and a causal research approach is used to identify the major aspects that raise personnel’ consciousness of HR Analytics. Findings:-This study gives current information about HR Analytics through the practice of HR Analytics in India which is minimal. The findings show that HR Analytics expertise is influenced by a variety of factors. Practical implications:-The study determined the level of HR Analytics understanding among managers from various sectors in India. To attain outstanding organizational performance, enterprises need implement the necessary HR Analytics. Originality/value:-The importance of the current study stems from the fact that just a few studies have looked into employee knowledge levels in the hands-on human resource analytics in India. Furthermore, the study makes an important contribution to the ongoing development of this field of study.